Adsorption material and method for adsorbing and extracting lithium

Through the collaborative adsorption technology of crosslinked polymer resin, the problems of low-efficiency and high cost of lithium adsorption in low-magnesium salt lake brine are solved, and efficient and environmentally friendly lithium recycling is achieved, which is suitable for industrial applications.

CN119318945APending Publication Date: 2025-01-17INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202310872702.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing adsorption materials have low lithium adsorption efficiency in low-magnesium salt lake brine, and are highly costly and polluted, making it difficult to achieve low-cost and efficient lithium recycling.

Method used

The crosslinked polymer resin is used as the adsorption material. Through the synergistic action of active adsorption groups and auxiliary adsorption groups, selective adsorption of calcium, magnesium and lithium is achieved, and the gas-liquid-solid three-phase reaction is used for desorption, simplifying the process process to reduce operating costs.

Benefits of technology

It realizes efficient lithium selective adsorption and purification, reduces the loss rate of adsorbent, and is suitable for lithium recovery in low-calcium magnesium salt lake brine, and has industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318945A_ABST
    Figure CN119318945A_ABST
Patent Text Reader

Abstract

The invention relates to an adsorption material and a method for adsorbing and extracting lithium. The adsorption material comprises cross-linked polymer resin; the cross-linked polymer resin comprises a polymer chain skeleton; the macromolecular chain skeletons are cross-linked through active adsorption groups. The adsorption material provided by the invention can selectively adsorb calcium and magnesium and selectively adsorb lithium, has an excellent adsorption effect and good selective adsorbability, can be desorbed by adopting a three-phase desorption technology, and is suitable for extracting lithium from low-calcium and low-magnesium salt lake brine through an adsorption method; the method for adsorbing and extracting lithium provided by the invention is simple in process and low in operation cost, can realize green and efficient lithium recovery of the low-calcium and low-magnesium salt lake, and is beneficial to industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium extraction, and in particular to an adsorption material and a method for extracting lithium by adsorption. Background Art

[0002] There are a large number of low-magnesium salt lake lithium resources in Tibet and South America. The concentration of lithium in salt lake resources is generally low, usually accompanied by a certain amount of calcium and / or magnesium, and a large amount of SO4 2- and CO3 2- etc., which brings great difficulties to lithium extraction technology. Adsorption lithium extraction technology has the characteristics of low environmental cost and simple process flow, and has significant advantages in lithium extraction technology. However, if lithium is directly adsorbed from brine containing a large amount of calcium and magnesium, the adsorption efficiency of lithium is generally less than 40%. In addition, in the field of lithium salt production and lithium secondary resource recovery, waste liquid containing low-concentration lithium and a large amount of other monovalent ions is often produced, especially solutions containing a large amount of sodium impurities. The presence of other monovalent ions such as sodium ions also interferes with lithium recovery.

[0003] At present, the types of commonly used adsorption materials mainly include alumina concentration difference adsorption analysis type and ion sieve type cation exchange adsorption analysis type. Among them, alumina-based adsorption materials are the most widely used and have good lithium selective adsorption. For example, CN107250049A discloses a porous activated alumina-based adsorbent for lithium extraction. The adsorbent adsorbs lithium in lithium-containing solutions through an activated alumina-lithium intercalation composition. However, this type of adsorption material is greatly affected by concentration differences, has low adsorption efficiency for low-magnesium and low-mineralization salt lake resources, and is affected by high-valent anions SO4. 2- and CO3 2- The impact of the ion sieve type lithium adsorption material is relatively large, which greatly limits its application in low-magnesium salt lake brine. The ion sieve type lithium adsorption material mainly includes manganate and titanate types, and its adsorption process is carried out in a neutral or alkaline system. For example, CN116099497A discloses a composite lithium adsorbent and a preparation method thereof. The preparation method adopts a one-step synthesis method to prepare alumina-loaded lithium manganese ion sieve to realize ion sieve molding, which can be used for alkaline lithium-containing solutions. However, this type of adsorption material needs to be desorbed with an acidic solution after use, which easily leads to a large dissolution rate of the ion sieve adsorption material, and the application cost is high, the pollution is serious, and the industrial application is difficult.

[0004] Therefore, it is of great significance to provide an adsorption material and a method for adsorption and extraction of lithium that have high selective adsorption capacity for lithium and are low in cost, stable in operation, and simple in regeneration process. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide an adsorption material and a method for extracting lithium by adsorption. Compared with the prior art, the adsorption material provided by the present invention can selectively adsorb calcium and magnesium as well as selectively adsorb lithium, has excellent adsorption effect, has good selective adsorption, can be desorbed by three-phase desorption technology, and is suitable for extracting lithium by adsorption from brine of low calcium and magnesium salt lakes; the production process is simple, the operating cost is low, and the green and efficient recovery of lithium from low calcium and magnesium salt lakes can be achieved, which is conducive to industrial application.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an adsorption material, the adsorption material comprising a cross-linked polymer resin;

[0008] The cross-linked polymer resin includes a polymer chain skeleton;

[0009] The polymer chain skeletons are cross-linked via active adsorption groups.

[0010] In the present invention, the adsorbent material anchors the active adsorption group through a cross-linked structure, which, on the one hand, utilizes the large porosity of the polymer material to increase the specific surface area of ​​adsorption; on the other hand, it avoids the loss of the adsorption material, facilitates the regeneration and reuse of the adsorption material, and is both environmentally friendly and economical; the active adsorption group also has good adsorption and selectivity, and more importantly, the adsorption material has a suitable pH value range in the adsorption of calcium and magnesium and lithium, and can use water and introduce carbon dioxide to carry out gas-liquid-solid three-phase reaction desorption, which has the obvious advantages of simple industrial application and low operating cost, and therefore has high application value.

[0011] Preferably, the cross-linked polymer resin includes resin A and resin B.

[0012] Preferably, the active adsorption groups of the resin A include carboxyl groups.

[0013] Preferably, the active adsorption group of the resin B includes a β-diketone structure.

[0014] In the present invention, resin A has a cross-linked structure with active adsorption group carboxyl, can selectively absorb calcium and / or magnesium, and has a high selectivity for calcium and / or magnesium. The initial purification of lithium can be achieved by treating a lithium source solution containing calcium and / or magnesium with resin A.

[0015] In the present invention, resin B has a cross-linked structure with an active adsorption group β-diketone structure, which can achieve excellent adsorption effect on lithium and has excellent selectivity for lithium in the presence of impurity elements such as sodium and potassium, thereby achieving purification and recovery of lithium.

[0016] Preferably, the crosslinking agent raw material used in the resin A includes one or a combination of any two of dodecanoic acid, isododecanoic acid, tridecanoic acid, isotridecanoic acid, tetradecanoic acid, isotetradecanoic acid, hexadecanoic acid, isohexadecanoic acid, octadecanoic acid, isooctadecanoic acid, eicosanoic acid or isoeicosanoic acid.

[0017] Preferably, the crosslinking agent raw material used in the resin B includes any one or a combination of at least two of dibenzoylmethane, 2-thenoyltrifluoroacetone, 1-phenyl-3-methyl-1-benzoyl-5-pyrazolone, benzoyl acetone, benzoyl isooctyl ketone, 2,4-pentanedione or benzoyl acetone dodecyl ketone.

[0018] Preferably, the polymer chain skeleton includes any one of polyethylene, polypropylene, polystyrene, polydivinylbenzene, polyvinyl chloride or polystyrene propylene, or a combination of at least two of them.

[0019] Preferably, the polymer chain skeletons are cross-linked via adsorption-assisting groups.

[0020] In the present invention, the role of introducing the adsorption-aiding group is to increase the synergistic coordination between the functional groups, thereby improving the activity of the adsorption group, increasing the adsorption rate, and allowing the metal adsorption to be carried out within a suitable pH range, and being able to use a three-phase reaction for desorption.

[0021] Preferably, the adsorption-aiding groups contained in the resin A include amide groups and / or ester groups.

[0022] Preferably, the adsorption-assisting groups contained in the resin B include any one of a phosphate group, an amide group or an alkyl phosphine oxide, or a combination of at least two of them.

[0023] Preferably, when the adsorption-aiding groups include phosphate groups, the cross-linking agent raw material used in the cross-linked polymer resin also includes tributyl phosphate.

[0024] Preferably, when the adsorption-aiding group includes an amide group, the crosslinking agent raw material used in the crosslinked polymer resin also includes any one of di-2, ethylhexyl lauramide, N,N-di(1-methylheptyl)hexanamide or 4-pyridine lauramide, or a combination of at least two thereof.

[0025] Preferably, when the adsorption-assisting group includes an alkylphosphine oxide, the cross-linking agent raw material used in the cross-linked polymer resin also includes a trialkylphosphine oxide.

[0026] Preferably, when the adsorption-aiding group includes an ester group, the cross-linking agent raw material used in the cross-linked polymer resin also includes 4-pyridine octyl ester.

[0027] Preferably, the mass of the active adsorption groups and the auxiliary adsorption groups in the cross-linked polymer resin accounts for 10-40% of the mass of the polymer chain skeleton, for example, it can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38% or 40%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In the present invention, it is preferred to control the percentage of the mass of the active adsorption groups and the auxiliary adsorption groups to the mass of the polymer chain skeleton within a specific range, which can further exert the synergistic effect between the adsorption groups and the polymer chain skeleton, thereby improving the adsorption capacity and selectivity for lithium.

[0029] In a second aspect, the present invention provides a method for extracting lithium by adsorption, wherein the method uses the adsorption material as described in the first aspect of the present invention.

[0030] The adsorption material provided by the present invention has high adsorption activity and selectivity, simple use and regeneration process, low operation cost, can realize lithium recovery, and is conducive to industrial application.

[0031] Preferably, the method comprises the following steps:

[0032] (1) using resin A to perform a first adsorption treatment on a lithium-containing solution to obtain a first lithium-extracting solution and a first adsorbed material, wherein the lithium-containing solution further contains calcium and / or magnesium;

[0033] (2) performing a second adsorption treatment on the first lithium extraction solution obtained in step (1) using resin B to obtain a second adsorbed material;

[0034] (3) The second adsorbed material obtained in step (2) is subjected to a three-phase desorption treatment by using water and continuously introducing carbon dioxide to obtain a second lithium extraction solution.

[0035] In the above method, resin A is first used to selectively adsorb calcium and / or magnesium to obtain a preliminarily purified first lithium extraction solution, and then resin B is used to selectively adsorb lithium to obtain a second adsorbed material containing lithium; thereafter, the second adsorbed material is subjected to a three-phase desorption treatment to obtain a purified lithium-rich solution, i.e., the second lithium extraction solution.

[0036] In the present invention, the source of the lithium-containing solution is not particularly limited, and may be, for example, lithium-containing salt lake brine or a solution produced during lithium production.

[0037] Preferably, the concentration of lithium in the lithium-containing solution is 0.1-1.0 g / L, for example, 0.1 g / L, 0.2 g / L, 0.5 g / L, 0.8 g / L or 1.0 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the concentration of calcium in the lithium-containing solution is 0.1-1.0 g / L, for example, it can be 0.1 g / L, 0.2 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.8 g / L or 1 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the concentration of magnesium in the lithium-containing solution is 0.1-1.0 g / L, for example, it can be 0.1 g / L, 0.2 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.8 g / L or 1 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the lithium-containing solution also contains sodium and / or potassium.

[0041] Preferably, the concentration of sodium in the lithium-containing solution is 10-120 g / L, for example, it can be 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L or 120 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the concentration of potassium in the lithium-containing solution is 1-20 g / L, for example, it can be 1 g / L, 2 g / L, 4 g / L, 6 g / L, 8 g / L, 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L or 20 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the pH value of the lithium-containing solution is 7-10, for example, 7, 7.5, 8, 8.5, 9, 9.5 or 10, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] Preferably, the first adsorbed material is subjected to three-phase desorption treatment by using water and continuously introducing carbon dioxide to obtain a desorption liquid containing calcium and / or magnesium.

[0045] Preferably, the pH value of the first lithium extraction solution is also adjusted before the second adsorption treatment.

[0046] Preferably, the pH value of the first lithium extraction solution in the second adsorption treatment is 10-13, for example, it can be 10, 10.5, 11, 11.5, 12, 12.5 or 13, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the concentration of lithium in the first lithium extraction solution is 0.1-1.0 g / L, for example, it can be 0.1 g / L, 0.2 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.8 g / L or 1 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the concentration of lithium in the second lithium extraction solution is 5-8 g / L, for example, it can be 5 g / L, 5.2 g / L, 5.5 g / L, 5.8 g / L, 6 g / L, 6.2 g / L, 6.5 g / L, 6.8 g / L, 7 g / L, 7.2 g / L, 7.5 g / L, 7.8 g / L or 8 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the second lithium extraction solution is subjected to precipitation reaction or heating pyrolysis to obtain a lithium carbonate product;

[0050] Preferably, the precipitating agent used in the precipitation reaction comprises sodium carbonate.

[0051] As a preferred technical solution of the second aspect of the present invention, the method comprises the following steps:

[0052] (1) using resin A to perform a first adsorption treatment on the lithium-containing solution to obtain a first lithium extraction solution and a first adsorbed material, wherein the lithium concentration in the first lithium extraction solution is 0.1-1.0 g / L, the lithium concentration in the lithium-containing solution is 0.1-1.0 g / L, the calcium concentration is 0.1-1 g / L, the magnesium concentration is 0.1-1 g / L, the sodium concentration is 10-120 g / L, the potassium concentration is 1-20 g / L, and the pH value is 7-10;

[0053] The first adsorbed material is subjected to three-phase desorption treatment using water and continuously introducing carbon dioxide to obtain a desorption liquid containing calcium and / or magnesium;

[0054] (2) performing a second adsorption treatment on the first lithium extraction solution obtained in step (1) using resin B to obtain a second adsorbed material; the pH value of the first lithium extraction solution in the second adsorption treatment is 10-13;

[0055] (3) treating the second adsorbed material obtained in step (2) with water and continuously introducing carbon dioxide for three-phase desorption to obtain a second lithium extraction solution;

[0056] The concentration of lithium in the second lithium extraction solution is 5-8 g / L, and the second lithium extraction solution is subjected to precipitation reaction or heating pyrolysis to obtain a lithium carbonate product.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The adsorption material provided by the present invention includes a cross-linked polymer resin having a diketone structure or a carboxyl group, and further cross-linking an auxiliary adsorbent to obtain an auxiliary adsorption group, which can not only increase the specific surface area of ​​adsorption, but also utilize the excellent adsorption capacity and selectivity of the active adsorption group and the auxiliary adsorption group. More importantly, it regulates the pH value range of metal ion adsorption, realizes the three-phase reaction desorption of carbon dioxide-water-solid adsorbent and the purification and recovery of lithium, avoids the loss of the adsorbent, and is more economical and environmentally friendly.

[0059] (2) The adsorption material provided by the present invention can be used to adsorb lithium in lithium-containing solutions, and is suitable for lithium-containing solutions with low calcium and magnesium contents, and is particularly suitable for extracting lithium from carbonate salt lake brine by adsorption. After adsorption, the three-phase reaction desorption technology is used for desorption. The use and regeneration process are simple, the operating cost is low, and the purification and recovery of lithium can be achieved, which is conducive to industrial application.

[0060] (3) Under optimal conditions, the adsorption material and the method for adsorption and extraction of lithium provided by the present invention have an adsorption rate of Mg of more than 91.4%, an adsorption rate of Ca of more than 80%, an adsorption rate of Li of more than 98%, a Li / Mg separation coefficient of more than 10.9, a Li / Ca separation coefficient of more than 4.7, a Li / Na separation coefficient of more than 320.00, a Li / K separation coefficient of more than 68.6, and a purity of lithium carbonate of more than 99.1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is an infrared spectrum of resin A described in Example 1 of the present invention;

[0062] Figure 2 It is the infrared spectrum of resin B described in Example 1 of the present invention. DETAILED DESCRIPTION

[0063] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0064] Example 1

[0065] This embodiment provides an adsorption material, the adsorption material includes a cross-linked polymer resin, the cross-linked polymer resin includes a polymer chain skeleton, the polymer chain skeletons are cross-linked by active adsorption groups and auxiliary adsorption groups, and the cross-linked polymer resin includes resin A and resin B;

[0066] The active adsorption group of the resin A is a carboxyl group, the auxiliary adsorption group is an ester group, and the crosslinking agent raw materials used in the resin A are dodecanoic acid and 4-pyridine octyl ester;

[0067] The active adsorption group of the resin B is a β-diketone structure, the auxiliary adsorption group is a phosphate group, and the crosslinking agent raw materials used in the resin B are dibenzoylmethane and tributyl phosphate;

[0068] The mass of the active adsorption groups and the auxiliary adsorption groups in the resin A and the resin B both account for 25% of the mass of the polymer chain skeleton.

[0069] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, the method comprising the following steps:

[0070] (1) using resin A to perform a first adsorption treatment on the lithium-containing solution to obtain a first lithium extraction solution and a first adsorbed material, wherein the lithium concentration in the first lithium extraction solution is 0.28 g / L, the lithium concentration in the lithium-containing solution is 0.30 g / L, the calcium concentration is 0.1 g / L, the magnesium concentration is 0.35 g / L, the sodium concentration is 120 g / L, the potassium concentration is 20 g / L, and the pH value is 9.5;

[0071] The first adsorbed material is subjected to three-phase desorption treatment using water and continuously introducing carbon dioxide for 20 minutes to obtain a desorption liquid containing calcium and magnesium;

[0072] (2) adjusting the pH value of the first lithium extraction solution obtained in step (1) to 12, and then performing a second adsorption treatment on the first lithium extraction solution using resin B to obtain a second adsorbed material;

[0073] (3) treating the second adsorbed material obtained in step (2) with water and continuously introducing carbon dioxide for three-phase desorption for 20 minutes to obtain a second lithium extraction solution;

[0074] The concentration of lithium in the second lithium extraction solution is 7.5 g / L. The second lithium extraction solution is heated to 90° C. and pyrolyzed for 1.5 hours to obtain a lithium carbonate product.

[0075] Example 2

[0076] This embodiment provides an adsorption material, the adsorption material includes a cross-linked polymer resin, the cross-linked polymer resin includes a polymer chain skeleton, the polymer chain skeletons are cross-linked by active adsorption groups and auxiliary adsorption groups, and the cross-linked polymer resin includes resin A and resin B;

[0077] The active adsorption group of the resin A is a carboxyl group, the auxiliary adsorption group is an ester group, and the crosslinking agent raw materials used in the resin A are isotetradecanoic acid and 4-pyridine octyl ester;

[0078] The active adsorption group of the resin B is a β-diketone structure, the auxiliary adsorption group is an alkyl phosphine oxide, and the crosslinking agent raw materials used in the resin B are benzoyl isooctyl ketone and trioctyl phosphine oxide;

[0079] The mass of the active adsorption groups and the auxiliary adsorption groups in the resin A and the resin B both account for 40% of the mass of the polymer chain skeleton.

[0080] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, the method comprising the following steps:

[0081] (1) using resin A to perform a first adsorption treatment on the lithium-containing solution to obtain a first lithium extraction solution and a first adsorbed material, wherein the lithium concentration in the first lithium extraction solution is 0.1 g / L, the lithium concentration in the lithium-containing solution is 0.1 g / L, the calcium concentration is 1.0 g / L, the magnesium concentration is 0.1 g / L, the sodium concentration is 10 g / L, the potassium concentration is 1 g / L, and the pH value is 10;

[0082] The first adsorbed material is subjected to three-phase desorption treatment using water and continuously introducing carbon dioxide for 30 minutes to obtain a desorption liquid containing calcium and magnesium;

[0083] (2) adjusting the pH value of the first lithium extraction solution obtained in step (1) to 11, and then performing a second adsorption treatment on the first lithium extraction solution obtained in step (1) using resin B to obtain a second adsorbed material;

[0084] (3) treating the second adsorbed material obtained in step (2) with water and continuously introducing carbon dioxide for three-phase desorption for 15 minutes to obtain a second lithium extraction solution;

[0085] The concentration of lithium in the second lithium extraction solution is 5 g / L, and the second lithium extraction solution is heated to 90° C. and pyrolyzed for 1.5 hours to obtain a lithium carbonate product.

[0086] Example 3

[0087] This embodiment provides an adsorption material, the adsorption material includes a cross-linked polymer resin, the cross-linked polymer resin includes a polymer chain skeleton, the polymer chain skeletons are cross-linked by active adsorption groups and auxiliary adsorption groups, and the cross-linked polymer resin includes resin A and resin B;

[0088] The active adsorption group of the resin A is a carboxyl group, the auxiliary adsorption group is an amide group, and the crosslinking agent raw materials used in the resin A are hexadecanoic acid and N,N-di(1-methylheptyl)hexamide;

[0089] The active adsorption group of the resin B is a β-diketone structure, the auxiliary adsorption group is an amide group, and the crosslinking agent raw materials used in the resin B are benzoyl acetone dodecyl ketone and 4-pyridine lauryl amide;

[0090] The mass of the active adsorption groups and the auxiliary adsorption groups in the resin A and the resin B both account for 10% of the mass of the polymer chain skeleton.

[0091] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, the method comprising the following steps:

[0092] (1) using resin A to perform a first adsorption treatment on the lithium-containing solution to obtain a first lithium extraction solution and a first adsorbed material, wherein the lithium concentration in the first lithium extraction solution is 1 g / L, the lithium concentration in the lithium-containing solution is 1 g / L, the calcium concentration is 0.3 g / L, the magnesium concentration is 1 g / L, the sodium concentration is 60 g / L, the potassium concentration is 3 g / L, and the pH value is 7;

[0093] The first adsorbed material is subjected to three-phase desorption treatment using water and continuously introducing carbon dioxide for 30 minutes to obtain a desorption liquid containing calcium and magnesium;

[0094] (2) adjusting the pH value of the first lithium extraction solution obtained in step (1) to 9, and then performing a second adsorption treatment on the first lithium extraction solution obtained in step (1) using resin B to obtain a second adsorbed material;

[0095] (3) treating the second adsorbed material obtained in step (2) with water and continuously introducing carbon dioxide for a three-phase desorption treatment for 30 minutes to obtain a second lithium extraction solution;

[0096] The concentration of lithium in the second lithium extraction solution is 8 g / L. The second lithium extraction solution is heated to 90° C. and pyrolyzed for 1.5 hours to obtain a lithium carbonate product.

[0097] Example 4

[0098] This embodiment provides an adsorption material. The only difference between the adsorption material and the embodiment 1 is that the mass of the active adsorption groups and the auxiliary adsorption groups in the resin B accounts for 5% of the mass of the polymer chain skeleton.

[0099] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Embodiment 1.

[0100] Example 5

[0101] This embodiment provides an adsorption material. The only difference between the adsorption material and the embodiment 1 is that the mass of the active adsorption groups and the auxiliary adsorption groups in the resin B accounts for 50% of the mass of the polymer chain skeleton.

[0102] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Embodiment 1.

[0103] Example 6

[0104] This embodiment provides an adsorption material. The only difference between the adsorbed material and Example 1 is that the polymer chain skeletons in resin A are cross-linked by active adsorption groups and do not contain auxiliary adsorption groups. The percentage of the mass of the active adsorption groups to the mass of the polymer chain skeleton is the same as that in Example 1.

[0105] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Embodiment 1.

[0106] Example 7

[0107] This embodiment provides an adsorption material. The only difference between the adsorbed material and Example 1 is that the polymer chain skeletons in resin B are cross-linked by active adsorption groups and do not contain auxiliary adsorption groups. The percentage of the mass of the active adsorption groups to the mass of the polymer chain skeleton is the same as that in Example 1.

[0108] This embodiment also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Embodiment 1.

[0109] Comparative Example 1

[0110] This comparative example provides an adsorption material. The only difference between the adsorbed material and Example 1 is that the polymer chain skeletons in resin A are cross-linked by auxiliary adsorption groups and do not contain active adsorption groups. The percentage of the mass of the auxiliary adsorption groups to the mass of the polymer chain skeleton is the same as that in Example 1.

[0111] This comparative example also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Example 1.

[0112] Comparative Example 2

[0113] This comparative example provides an adsorption material. The only difference between the adsorbed material and Example 1 is that the polymer chain skeletons in resin B are cross-linked by auxiliary adsorption groups and do not contain active adsorption groups. The percentage of the mass of the auxiliary adsorption groups to the mass of the polymer chain skeleton is the same as that in Example 1.

[0114] This comparative example also provides a method for extracting lithium by adsorption using the above-mentioned adsorption material, and the method is the same as that in Example 1.

[0115] The resin A and resin B in Examples 1-7 and Comparative Examples 1-2 were subjected to infrared spectroscopy. Taking Example 1 as an example, the infrared spectrum of resin A is as follows: Figure 1 As shown, from Figure 1 It can be seen that at 1700cm -1 The characteristic absorption peak of carboxyl group appears at 1260m -1 The characteristic absorption peak of ester group appears at Figure 2 As shown, from Figure 2 It can be seen that at 1706cm -1 、1733cm -1 The characteristic absorption peak of β-diketone appears at 1300 cm -1 The characteristic absorption peak of phosphate group appears at

[0116] ICP-AES was used to measure the content of each ion in the first lithium extraction solution and the second lithium extraction solution in Examples 1-7 and Comparative Examples 1-2, as shown in Table 1; and the adsorption rates of magnesium, calcium, and lithium were calculated, and the adsorption rate was equal to the adsorption efficiency multiplied by the desorption efficiency, and the results are shown in Table 2.

[0117] Calculate the separation factor: Separation factor = [C-Li (0) / C-Li (f) ] / [Cimp (0) / Cimp (f) ];

[0118] Among them, C-Li (0) is the concentration of lithium in the starting solution; C-Li (f) is the concentration of lithium in the solution after adsorption and desorption treatment; Cimp (0) is the concentration of impurity elements (such as Mg, Ca, Na, K) in the starting solution; Cimp (f) is the concentration of impurity elements in the solution after adsorption and desorption treatment. The results are shown in Table 2.

[0119] The purity of lithium carbonate was calculated by dissolving the lithium carbonate product and determining the mass of lithium carbonate therein, and calculating the percentage of the mass of the lithium carbonate obtained to the mass of the lithium carbonate product. The results are shown in Table 2.

[0120] Table 1

[0121]

[0122]

[0123] Table 2

[0124]

[0125] *Indicates data not available.

[0126] The following points can be seen from the data in Table 1-2:

[0127] (1) From the data of Examples 1-3, it can be seen that under optimal conditions, the adsorption rate of Mg for the adsorption material and the method for adsorption and extraction of lithium provided by the present invention reaches more than 91.4%, the adsorption rate of Ca reaches more than 80%, the adsorption rate of Li reaches more than 98%, the Li / Mg separation coefficient reaches more than 10.9, the Li / Ca separation coefficient reaches more than 4.7, the Li / Na separation coefficient reaches more than 320.00, the Li / K separation coefficient reaches more than 68.6, and the purity of lithium carbonate reaches more than 99.1%.

[0128] (2) A comprehensive comparison of the data of Example 1 and Examples 4-5 shows that the only difference between Example 4-5 and Example 1 is that the mass ratio of the active adsorption group and the auxiliary adsorption group is not within the preferred range of the present invention. In Example 1, not only the adsorption rates of Mg, Ca, and Li are significantly higher than those of Examples 4-5, but also the separation coefficient of lithium relative to impurity ions is greatly improved, and the purity of the obtained lithium carbonate is significantly increased. It can be seen that the present invention preferably controls the mass ratio of the active adsorption group and the auxiliary adsorption group within a specific range, which can further improve the adsorption performance and selectivity of the adsorption material.

[0129] (3) Comprehensive comparison of the data of Example 1, Examples 6-7 and Comparative Examples 1-2 shows that the only difference between Example 6 and Comparative Example 1 compared with Example 1 is that the resin A contains only active adsorption groups and auxiliary adsorption groups, and the only difference between Example 7 and Comparative Example 2 compared with Example 1 is that the resin B contains only active adsorption groups and auxiliary adsorption groups, and the adsorption rate of Mg and Ca in Example 1 is significantly better than that of Example 6 and Comparative Example 1, and the adsorption rate of lithium in Example 1 is significantly better than that of Example 7 and Comparative Example 2, and lithium carbonate cannot be obtained in Comparative Examples 1-2. It can be seen that the present invention can improve the adsorption effect and achieve purification and recovery of lithium through the synergistic effect of active adsorption groups and auxiliary adsorption groups.

[0130] In summary, the adsorption material and the method for extracting lithium by adsorption provided by the present invention can selectively adsorb calcium and magnesium as well as selectively adsorb lithium, have excellent adsorption effect, have good selective adsorption properties, and are conducive to the purification and recovery of lithium.

[0131] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An adsorption material, characterized in that: The adsorption material includes a cross-linked polymer resin; The cross-linked polymer resin includes a polymer chain skeleton; The polymer chain skeletons are cross-linked via active adsorption groups.

2. The adsorption material according to claim 1, characterized in that The cross-linked polymer resin includes resin A and resin B; The active adsorption groups of the resin A include carboxyl groups; The active adsorption group of the resin B includes a β-diketone structure.

3. The adsorption material according to claim 2, characterized in that The crosslinking agent raw material used in the resin A includes one or a combination of any two of dodecanoic acid, isododecanoic acid, tridecanoic acid, isotridecanoic acid, tetradecanoic acid, isotetradecanoic acid, hexadecanoic acid, isohexadecanoic acid, octadecanoic acid, isooctadecanoic acid, eicosanoic acid or isoeicosanoic acid; Preferably, the crosslinking agent raw material used in the resin B includes any one or a combination of at least two of dibenzoylmethane, 2-thenoyltrifluoroacetone, 1-phenyl-3-methyl-1-benzoyl-5-pyrazolone, benzoyl acetone, benzoyl isooctyl ketone, 2,4-pentanedione or benzoyl acetone dodecyl ketone; Preferably, the polymer chain skeleton includes any one of polyethylene, polypropylene, polystyrene, polydivinylbenzene, polyvinyl chloride or polystyrene propylene, or a combination of at least two of them.

4. The adsorption material according to any one of claims 1 to 3, characterized in that: The polymer chain skeletons are also cross-linked through adsorption-assisting groups; Preferably, the adsorption-assisting groups contained in the resin A include amide groups and / or ester groups; Preferably, the adsorption-assisting groups contained in the resin B include any one of a phosphate group, an amide group or an alkyl phosphine oxide, or a combination of at least two of them.

5. The adsorption material according to claim 4, characterized in that When the adsorption-assisting groups include phosphate groups, the cross-linking agent raw material used in the cross-linked polymer resin also includes tributyl phosphate; Preferably, when the adsorption-assisting group includes an amide group, the crosslinking agent raw material used in the crosslinked polymer resin further includes any one of di-2, ethylhexyl lauramide, N, N-di(1-methylheptyl)hexanamide or 4-pyridine lauramide or a combination of at least two thereof; Preferably, when the adsorption-assisting group includes an alkylphosphine oxide, the crosslinking agent raw material used in the crosslinked polymer resin also includes a trialkylphosphine oxide; Preferably, when the adsorption-aiding group includes an ester group, the cross-linking agent raw material used in the cross-linked polymer resin also includes 4-pyridine octyl ester.

6. The adsorption material according to any one of claims 1 to 5, characterized in that: The mass of the active adsorption groups and the auxiliary adsorption groups in the cross-linked polymer resin accounts for 10-40% of the mass of the polymer chain skeleton.

7. A method for extracting lithium by adsorption, characterized in that: The method for extracting lithium by adsorption adopts the adsorption material as described in any one of claims 1-6.

8. The method according to claim 7, characterized in that The method comprises the following steps: (1) using resin A to perform a first adsorption treatment on a lithium-containing solution to obtain a first lithium-extracting solution and a first adsorbed material, wherein the lithium-containing solution further contains calcium and / or magnesium; (2) performing a second adsorption treatment on the first lithium extraction solution obtained in step (1) using resin B to obtain a second adsorbed material; (3) The second adsorbed material obtained in step (2) is subjected to a three-phase desorption treatment by using water and continuously introducing carbon dioxide to obtain a second lithium extraction solution.

9. The method according to claim 8, characterized in that The concentration of lithium in the lithium-containing solution is 0.1-1.0 g / L; Preferably, the concentration of calcium in the lithium-containing solution is 0.1-1 g / L; Preferably, the concentration of magnesium in the lithium-containing solution is 0.1-1 g / L; Preferably, the lithium-containing solution also contains sodium and / or potassium; Preferably, the concentration of sodium in the lithium-containing solution is 10-120 g / L; Preferably, the concentration of potassium in the lithium-containing solution is 1-20 g / L; Preferably, the pH value of the lithium-containing solution is 7-10; Preferably, the first adsorbed material is subjected to three-phase desorption treatment using water and continuously introducing carbon dioxide to obtain a desorption liquid containing calcium and / or magnesium; Preferably, the pH value of the first lithium extraction solution is further adjusted before the second adsorption treatment; Preferably, the pH value of the first lithium extraction solution in the second adsorption treatment is 10-13; Preferably, the concentration of lithium in the first lithium extraction solution is 0.1-1.0 g / L.

10. The method according to claim 8 or 9, characterized in that: The concentration of lithium in the second lithium extraction solution is 5-8 g / L; Preferably, the second lithium extraction solution is subjected to precipitation reaction or heating pyrolysis to obtain a lithium carbonate product; Preferably, the precipitating agent used in the precipitation reaction comprises sodium carbonate.

Citation Information

Patent Citations

  • Porous activated alumina based sorbent for lithium extraction

    CN107250049A

  • Composite lithium adsorbent and preparation method thereof

    CN116099497A

Cited By

  • Beta-diketone resin and preparation method thereof, beta-diketone extraction resin and preparation method and application thereof

    CN121005805A